Determinants of Young Zalo Users’s Satisfaction: The Case of Young People Living in Ho Chi Minh City, Vietnam - Nguyen Thi Cam Loan; Truong Thi Thuy Vi (International Journal of Small and Medium Enterprises and Business Sustainability, 2022)
This study identifies the determinants of young Zalo users’ satisfaction, conducted by qualitative research combining quantitative research. Survey data was collected from 100 young respondents living in Ho Chi Minh City. Accordingly, determinants of young Zalo users’ satisfaction in the descending order of the level of influence are convenience, perceived usefulness, design, trust and perceived ease of use. The study is a scientific basis for suggesting solutions for the marketing department of Zalo to attract more users in the current period.